THE METHOD OF JITTER DETERMINING IN THE TELECOMMUNICATION NETWORK OF A COMPUTER SYSTEM ON A SPECIAL SOFTWARE PLATFORM - Mykhailo Mozhaiev; Nina Kuchuk; Maksym Usatenko (Сучасний стан наукових досліджень та технологій в промисловості, 2019)
Relevance of the study: When choosing a platform, the quality criteria for computer system service depend significantly on the parameters of the basic telecommunications network. Therefore, the telecommunications network has strict requirements. In addition, the network must satisfy a number of constraints that are set by the computer system. Only the fulfillment of these conditions will allow the computer system to solve its tasks. Also, when constructing, modifying and operating telecommunication networks, there is a rather common problem with no digital signal processing, network synchronization and stability. The tasks of ensuring temporary requirements for system transactions: it is necessary to find the most significant QoS parameters that allow dynamic network reconfiguration to ensure the fulfillment of temporary requirements for system transactions. Subject of study: jitter of the telecommunication network. The purpose of the article is to develop a method of prompt calculation of jitter values of a telecommunication network for dynamic adjustment of network parameter. Results of the study: The analysis of the influence of nonstationarity of data transmission in the telecommunication subsystem of the investigated computer system was carried out. The classification of jitter and causes leading to its occurrence has been made. The results of the analysis of the factors that improve the quality of data transmission in the network due to the operational jitter frequency calculation are presented. Researches of the resolution characteristics of coherent acousto-optic spectro-analysers are carried out in the work. Analytical ratios for the output signal were obtained for two monochromatic radio signals at the input, taking into account the effects of nonlinear interaction of the output signals and the a priori dependence of the location and width of the diffraction spot on the frequency of the investigated signal. The most significant qualitative and quantitative characteristics of frequency separation are shown in the example of two monochromatic signals, which differ only in carrier frequencies. These analytical ratios were experimentally verified by simulation of the system. Conclusions. As a result of the research, a method of increasing the resolution of acousto-optic spectro analyzers was proposed due to the features of coherent signal interaction in the frequency jitter computation process. It is based on the method of operative calculation of jitter value of telecommunication network, which allows performing dynamic adjustment of network parameters.